PENGARUH KARAKTERISTIK ANGGARAN TERHADAP PRESTASI MANAJER - Suparman Hadi (Akutansi Bisnis & Manajemen ( ABM ), 2001)
This study has its rationale the fact that Village Unit Cooperative (VUC) as a socio-economical organization, on the one hand operates based on the principles of productiveness, efecteveness, efficiency and cares about gaining profit. On the other, it cares about welfare of its members. Therefore, a manager is expected to perform optimally. A managers performance is not only measured by the main product profitability, but by the attitude of staff as well. Therefore, this study is mainly aimed at determining the influence of variables of budget characteristics on profitability level and staffs attitude. Twenty-three VUC managers were taken as sample by random sampling technique. Considering that the attitude variable had to be extracted from the staff, from each VUC three staff were selected by simple random sampling dispropotional technique. The analysis was based on correlation and multi-linear regression. The result of the syudy indicate that simultaneously, the influence on profitability was R2=0.721 and on staffs attitude was R2=0.692. Partially, the influence of the variables of budget characteristics on profitability an staffs attitude varied. The variables profitability with significant influence was evidence of the participation in the budget arranggement (b1=0.150), p=0.0001), budget target clarity (b2=0.068, p=0.0007), and budget evaluation (b4=0.0047, p=0.035). Those without significant influence was shown by the budget evaluation (b4=0.731, p=0.341), and budget difficulty level (b5=1.029, p=0.170). Direct influence was revealed between the variables of budget characteristics and staffs attitude. Therefore, it is suggested that future study in this field focus on managerial human resource, in term of work motivation, and satisfaction, in particular. Only by a soud understanding of the internal aspects of individual could this matter be explained